ABDI DALEM KERATON SURAKARTA HADININGRAT TAHUN 2004-2014 - Kristiyanto, Dani Eko; Yusuf, Syafruddin; Syair, Alian (Journal of Indonesian History, 2019)
This research is entitled "Courtiers of Surakarta Hadiningrat Palace in 2004-2014". This research aims to find out the meaning of ?Mengabdi" or ?subserve? the Courtiersof the Kasunanan Surakarta Hadiningrat Palace, especially the Courtiersof Bondet after the abolition of the Surakarta Regional Privileges under Law No. 32 of 2004. This research used the Historical method with a qualitative sociological and anthropological approach. Courtiers of the Kasunanan Surakarta Hadiningrat Palace became the main informant in this research, and integrated with a literature review that has been done before. The technique of data collection is done by literature review, observation, in-depth interviews, and documentation. Research steps done by heuristcs, external, internal criticism, interpretation and historiography. The results of the research show that the based on Law No. 32 of 2004 both the Surakarta court and the duties and functions of the countiers did not experience any changes and changes because meaning of "subserve" of the courtiers had a strong philosophy of life, they all strive fora total and loyaldevotion to their Sinuhun, whatever happens loyalty remains the main thing that must be upheld, here is where they taught the true meaning of life does not merely a matter of wealth, but the achievement of real inner satisfaction, even though the situation was rough, they were still grateful for it, because they hold fast to the Javanese philosophy of "Nerimo Ing Pandum", it was what they wanted to maintained and bequeathed to the next generation. Keywords: Courtiers of Surakarta Hadiningrat Palace, Courtiers of Bondet.